2021
DOI: 10.3389/fnins.2021.695653
|View full text |Cite
|
Sign up to set email alerts
|

Squamous and Respiratory Metaplasia After Olfactory Mucosal Resection

Abstract: Resection of the olfactory mucosa (OM) is sometimes unavoidable during surgery; however, it is not known whether the OM can completely recover thereafter. The aim of this study was to uncover whether the OM fully recovers after mucosal resection and describe the process of OM regeneration. 8-week-old male Sprague–Dawley rats (n = 18) were subjected to OM resection at the nasal septum; six rats were euthanized for histological examination 0, 30, and 90 days after surgery. Immunohistochemistry was performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The authors observed regeneration of the OE after 30 days followed by its degeneration into squamous or ciliated epithelia after 90 days with presence of connective tissue [82]. Furthermore, the influx of macrophages in the tissue was higher after 90 days than after 30 days, questioning the role of inflammation in metaplasia [82]. This OE metaplasia was also shown in a rat lesioned OE.…”
Section: Other Potential Mechanistic Driversmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors observed regeneration of the OE after 30 days followed by its degeneration into squamous or ciliated epithelia after 90 days with presence of connective tissue [82]. Furthermore, the influx of macrophages in the tissue was higher after 90 days than after 30 days, questioning the role of inflammation in metaplasia [82]. This OE metaplasia was also shown in a rat lesioned OE.…”
Section: Other Potential Mechanistic Driversmentioning
confidence: 96%
“…Results also showed differences in the number of normal OSNs with 24% in CRS patients compared to 45% in healthy controls as well as a more severe erosion of the OE in CRS patients [81]. A more recent study observed OE regeneration after surgical lesion of rat OE [82]. Resections of the olfactory mucosa present on the nasal septum were analysed by immunohistochemistry at 0, 30, and 90 days after surgery.…”
Section: Other Potential Mechanistic Driversmentioning
confidence: 99%
See 1 more Smart Citation